2001
DOI: 10.1128/iai.69.1.45-51.2001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus agrGenotypes with Enterotoxin Production Capabilities Can Resist Neutrophil Bactericidal Activity

Abstract: Staphylococcus aureus pathogenicity is mainly due to the production of a number of secreted and cell surface-associated proteins under the regulation of the agr gene. A region of the agr gene was used to subgroup S. aureus strains according to restriction fragment length polymorphisms. Additionally, strains were subtyped according to the coagulase gene in order to strengthen discriminatory power. Virulence capabilities of agr genotype subgroups were evaluated using an in vitro neutrophil bactericidal assay, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
1
41
0
2
Order By: Relevance
“…tions within groups were also found (20,25,28,29). In this work, we identified 14 different agr restriction types among the analyzed strains.…”
Section: Discussionmentioning
confidence: 77%
“…tions within groups were also found (20,25,28,29). In this work, we identified 14 different agr restriction types among the analyzed strains.…”
Section: Discussionmentioning
confidence: 77%
“…S. aureus was isolated (one strain per subject) from 96 of 275 (35%) children and from 64 of 225 (28%) guardians (13). agr specificity groups were identified by PCR amplification of the hypervariable domain of the agr locus using oligonucleotide primers specific for each of the four major specificity groups (obviating the need for restriction fragment length polymorphism analysis commonly employed in previous studies [7,10,14]). A forward primer, pan-agr (5Ј-ATGCACATGGTGCACATGC-3Ј), corresponding to conserved sequences from the agrB gene, was used in all reactions (Fig.…”
mentioning
confidence: 99%
“…This type of bacterial interference is unusual, because it affects the expression of a subset of genes rather than inhibiting growth. Diverse works have noted the existence of distinct agr alleles, as defined with agr restriction fragment length polymorphism, within agr groups both in clinical S. aureus isolates that originated with humans and in those from cows (2,15,16,19,24,29). In a recent study, one of us identified 12 distinct agr alleles in an epidemiologically unrelated collection of bovine mastitis isolates.…”
mentioning
confidence: 99%